The association between adherence to levothyroxine and economic and clinical outcomes in patients with hypothyroidism in the US. (2nd September 2018) - Hepp, Zsolt; Lage, Maureen J.; Espaillat, Ramon; Gossain, Ved V.
Abstract: Objective: To evaluate outcomes associated with adherence to levothyroxine (LT4) in the US adult hypothyroidism population. Methods: We used data from Truven's MarketScan databases from 1 July 2011 through 31 December 2015. Patients aged 18 or older were diagnosed with hypothyroidism (confirmed at least twice) and prescribed LT4. Patients were excluded if they did not have continuous insurance coverage or if they received a diagnosis of thyroid cancer or pregnancy during the study period. Multivariable analyses on a matched cohort of adherent and nonadherent patients examined the relationships among patient outcomes and adherence, defined as the proportion of days covered ≥80%. Outcomes included all-cause and hypothyroidism-related medical costs and resource utilization and comorbid diagnoses measured over the 1 year post-period following the first prescription for LT4. The analyses controlled for patient age, sex, region of residence, type of insurance coverage, diagnosing physician and pre-period general health status as proxied by the Charlson Comorbidity Index. Results: Prior to matching, there were 168, 457 patients identified as adherent and 198, 443 patients identified as nonadherent. The matched cohort consisted of 318, 628 individuals, with equal numbers of adherent and nonadherent patients ( n = 159, 314). Patients who were adherent used significantly fewer resources and had significantly lower all-cause (14, 136 vs. 14, 926; p < .0001) and hypothyroidism-related (1672 vs. 1709; p < .0001) total costs, although the costs of drugs were higher in the adherent group. Furthermore, adherent patients, compared to nonadherent patients, were significantly less likely to be diagnosed with comorbid Addison's disease, bipolar disorder, chronic kidney disease, depression, migraine, obesity, type 1 diabetes or type 2 diabetes during the follow-up period. Conclusions: Compared to nonadherence, adherence to LT4 among patients with hypothyroidism was associated with a significant reduction in all-cause and hypothyroidism-related costs and resource utilization as well as significantly lower rates of many comorbid diagnoses.